Perceptions of medical students on a three-step teaching approach to promote active learning in embryology - Smitha Elizabeth Kore; Gulam Saidunnisa Begum (Wolters Kluwer Medknow Publications, 2022)
Background: The study of embryology is an essential component of the anatomy course during the preclinical years of medical education. It is usually perceived as difficult to comprehend due to the rapid three-dimensional changes that occur during fetal life. Visual representation while explaining the developmental process can facilitate comprehension. Active discussion with peers is another important learning aid that can help with better retention of the concepts taught in embryology. The present study was conducted with an objective to evaluate perceptions about the three-step active learning in embryology using "do it yourself (DIY) construction models" as props, reciprocal peer tutoring (RPT) sessions, and case discussions. Methodology: A descriptive cross-sectional study was conducted on 80 students attending the embryology lecture on the gastrointestinal tract development. In step-1, the traditional lecture was delivered using a PowerPoint presentation which was complemented by three-dimensional (3D) visualization using "DIY" construction models used as props. Step-2 RPT session step-3 application exercises using real-time cases. Feedback was taken on a questionnaire administered using a 5-point Likert scale. Results: The descriptive analysis of the feedback revealed that most of the students were satisfied with the different active teaching strategies employed to conduct the sessions. The Chi-square test analysis showed a significant association between the questions posed in the feedback questionnaire. Conclusion: Our study provides insights into the importance of multiple active teaching techniques in learning embryology. The impact usage of props (DIY models) enhanced comprehension, peer teaching sessions helped the students to bridge the cognitive gaps, and case-based learning promoted critical thinking, and problems-solving skills.